RANCANG BANGUN SISTEM INFORMASI MONITORING DAN ANALISIS KINERJA PENJUALAN MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT ( RAD ) - Rasim, Rasim; Mugiarso, Mugiarso; Handayani, Dwipa; Lubis, Hendarman (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The sales achievement monitoring process at CV Pakar Prima Buana, which relies on Microsoft Excel, has led to issues such as data duplication and inconsistency due to the manual filtering and target distribution performed by team leaders in a company with over 500 employees. This study aims to develop a web-based information system designed to simplify, accelerate, and streamline the monitoring of each salesperson’s achievement performance. The Rapid Application Development (RAD) methodology was adopted for its fast and adaptive development cycle, consisting of three main phases: Requirements Planning, Design Workshop, and Implementation. The system was developed using PHP, the CodeIgniter framework, and a MySQL database. The black-box testing results demonstrate that all system functions operate as expected. The resulting system successfully automates the calculation and reporting of sales achievements, eliminates data duplication, and provides structured, accurate, and timely information to support managerial decision-making. Keywords: Information System, Sales Achievement, Rapid Application Development, CodeIgniter, Black-box Testing